Perubahan Tekstur, Aktivitas Air, dan Sifat Termal Dodol selama Penyimpanan sebagai Pengaruh Proporsi Santan Kelapa dan Suhu Penyimpanan - Setiavani, Gusti; Sugiyono, Sugiyono; Suyatma, Nugraha Edhi (Jurnal Teknologi dan Industri Pangan, 2024)
Dodol is an Indonesia's traditional food made from a certain combination of glutinous rice flour, coconut milk, and palm sugar. Its stability and structure during storage changed greatly due to rheological characteristics, which was dependent on the proportion of raw materials and storage conditions. This study aimed to examine changes in texture (hardness, cohesiveness, springiness, and adhesiveness), water activity, and thermal properties of dodol during storage, as well as the correlation between these parameters. A factorial design was used with two factors (proportion of coconut milk and storage temperatures) and the samples were observed over 15 days. In terms of texture, hardness and adhesiveness rose, while cohesiveness and springiness declined. Such changes were influenced by the two factors studied. Water activity and thermal properties also varied, with enthalpy changes linked to retrogradation, particularly at refrigerator temperatures. A strong correlation was found between enthalpy changes and hardness, but a weak linear correlation between enthalpy and water activity. This study concluded that the proportion of coconut milk and storage temperature became two crucial factors determining the changes in texture, water activity, and thermal properties of dodol during storage.